2014
DOI: 10.18553/jmcp.2014.20.12.1246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Intravenous Trimethoprim/Sulfamethoxazole Shortage on Treatment Outcomes Among HIV-Infected Patients with Pneumocystis jirovecii Pneumonia

Abstract: BACKGROUND: Trimethoprim/sulfamethoxazole (TMP/SMX) is the recommended first-line treatment for human immunodeficiency virus (HIV)-infected patients with Pneumocystis jirovecii pneumonia (PJP). However, in June 2010, the lone manufacturer of intravenous (IV) TMP/SMX in the United States stopped production of this medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…One study, Abdelrahman et al [36] reported both increased and equivalent mortality, the majority of physicians agreed or were neutral regarding the statement that drug shortages resulted in patient deaths, however, there was also a proportion of physicians which disagreed. Medication classes that were commonly involved in poor patient outcomes during shortages included antimicrobials [28, 33, 3739] and oncology medicines [2427, 31, 32, 4042].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study, Abdelrahman et al [36] reported both increased and equivalent mortality, the majority of physicians agreed or were neutral regarding the statement that drug shortages resulted in patient deaths, however, there was also a proportion of physicians which disagreed. Medication classes that were commonly involved in poor patient outcomes during shortages included antimicrobials [28, 33, 3739] and oncology medicines [2427, 31, 32, 4042].…”
Section: Resultsmentioning
confidence: 99%
“…Adverse drug reactions (ADRs) were reported in 24 studies. Of these, 14 reported increased ADRs [7, 13, 22, 2226, 28, 33, 37, 38, 40, 43, 44], six reported equivalent incidences of ADRs [8, 31, 32, 35, 41, 45], and one reported decreased ADRs due to the shortages [16]. Three studies reported multiple impacts on ADRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no increased mortality noted while the shortage lasted. 94 For patients with severe disease, however, IV therapy is preferred to improve the likelihood that appropriate serum levels of the drug will be attained. TMP-SMX is less well tolerated among patients with HIV/ AIDS than among those with other underlying diseases.…”
Section: Treatment Of Pneumocystis Pneumoniamentioning
confidence: 99%
“…Finally, in a study of the impact of an intravenous trimethoprim/sulfamethoxazole shortage on treatment outcomes with Pneumocystis jirovecii pneumonia, Dilworth and colleagues found that more patients experienced treatment failure, worsening clinical status, and had slightly longer length of stay during the shortage as compared to the pre-shortage period. 9 It was suggested that, although the negative impact on patient outcomes was immediate, collaboration between pharmacists and physician caregivers improved outcomes and lessened the global impact of the shortage. The patient outcomes in this study are in contrast to our finding of a significantly decreased length of stay during the pre-shortage group and the findings of no difference between groups in length of therapy, days of therapy, and ICU status.…”
mentioning
confidence: 99%